Mental Multimorbidity Among General-Population Adults: Sex-Specific Sociodemographic Profiles of Anxiety, Insomnia, and Eating Disorders - Valentina A. Andreeva; Nathalie Arnault; Stéphanie Chambaron; Cécilia Samieri; Marie-Claude Brindisi; Pauline Duquenne; Serge Hercberg; Pilar Galan; Mathilde Touvier; Leopold K. Fezeu (Frontiers Media S.A., 2024)
ObjectiveTo determine the prevalence and sociodemographic profiles of mental morbidity and multimorbidity.MethodsA descriptive analysis was performed with data from 25,269 women and 8,389 men from the French NutriNet-Santé general-population cohort. Participants were split into 8 groups: 1. No mental morbidity; 2. Pure anxiety; 3. Pure insomnia; 4. Pure eating disorders (ED); 5. Comorbid anxiety and insomnia; 6. Comorbid anxiety and ED; 7. Comorbid insomnia and ED; 8. Multimorbid anxiety, insomnia, and ED. Data were weighted using the 2016 French Census and analyzed with Chi2 tests.Results40.6% of the participants had ≥1 mental disorder; 2.3% had all 3 disorders. Most pure and comorbid disorders were more common in women than in men. The multimorbidity group had the largest proportions of men who were overweight (52.1%) and current smokers (23.2%). Men with insomnia and ED were the most likely to have obesity (45.8%) and low physical activity (44.3%). Women with ≥2 disorders were the most likely to be current smokers.ConclusionThe findings could inform research, prevention, and public health guidelines for multimorbidity.